Transition metal carbonitride-SiCxNy composite ceramic and preparation method thereof
Through the preparation method of complex phase ceramics of transition metal disilicate and carbon powder, SiCxNy ceramic phase is generated, which solves the problems of harsh preparation conditions and insufficient performance of HfCxNy ceramics, improves the strength and ablation resistance of complex phase ceramics, and achieves more Wide range of high temperature applications.
Patent Information
- Application Number
- CN202411301495.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The preparation conditions of existing HfCxNy ceramics are harsh and the application performance is insufficient. The intrinsic brittleness and insufficient oxidation resistance of single-phase ultra-high temperature ceramics limit the engineering application of materials.
The composite phase ceramic preparation method of transition metal disilicate (MeSi2) and carbon powder is used to produce transition metal carbon nitride-SiCxNy composite phase ceramics through ball milling, cold pressing and high-temperature heat treatment under nitrogen environment, and the SiCxNy ceramic phase is used to improve sintering Performance and mechanical properties.
It improves the strength, toughness and ablation resistance of composite ceramics, achieves a wider application in high-temperature domains, reduces the production cost, and shows excellent ablation resistance under high-temperature oxygen-containing environments.
Smart Images

Figure CN119191848A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of transition metal carbonitride composite ceramics and relates to a transition metal carbonitride-SiC x N y Composite ceramics and preparation methods thereof. Background Art
[0002] As high-speed aircraft develop towards higher Mach, longer flight time and larger airspace, aircraft are subjected to extreme temperature differences and harsh aerodynamic / thermal environments during service, which puts more stringent requirements on thermal protection materials - more resistant to high temperatures, more load-bearing, and more erosion-resistant to ensure safety and reliability during flight. Ultra-high temperature ceramics, mainly referring to carbides, nitrides and borides of transition metals of group IVB and group VB, have excellent physical and chemical properties such as high melting point, high hardness, high modulus, high temperature resistance and good corrosion resistance. They have become important non-ablative thermal protection materials and are widely used in the nose tip, leading edge of the fuselage and key hot end components of the combustion chamber of ramjet engines of high-speed aircraft. In the hypersonic aircraft tests of SHARPB-1 and B-2 models and related NASA reports, ultra-high temperature ceramics were identified as candidate materials for key thermal structural components of hypersonic aircraft. Studies have shown that the introduction of N atoms into the C sublattice of carbide ultra-high temperature ceramics can further improve the high temperature stability and ablation resistance of carbide ceramics, especially HfC x N y The ceramic system is predicted to have the highest melting point and is expected to be used in ultra-high temperature environments above 3000°C.
[0003] Currently, researchers have studied HfC x N y The preparation of powder or bulk ceramics was studied. Reference 1 "Zhang Xintao, Xu Jingjun, Qian Yuhai, et al. Synthesis and characterization of novel single-phase HfC x N 1-x Ceramic powders[J].Materials Chemistry and Physics, 2023, 295:127099. "Hf, HfN, and C powders were used as raw materials and induction heated to 2400°C for 30 minutes to prepare HfC x N 1-xPowder. Reference 2 "Peng Zheng. Design, preparation and ablation resistance of ultra-high temperature hafnium carbonitride ceramics and their composites [D], 2022." Using high-purity HfC and HfN powders as raw materials, g-C3N4 powder as supplementary carbon source and nitrogen source, spark plasma sintering method and 20MPa pressure were applied, and the temperature was kept at 2200℃ for 20min to prepare ultra-high temperature HfC with a density of more than 99%. x N y However, HfC x N y The preparation conditions of ceramics are harsh and the preparation cost is high. In addition, single-phase ultra-high temperature ceramics have high intrinsic brittleness and insufficient oxidation resistance, which limits the engineering application of materials. Summary of the invention
[0004] The present invention aims to provide a transition metal carbonitride-SiC x N y Composite ceramics and preparation methods thereof solve the problems of HfC in the prior art x N y The preparation conditions of ceramics are harsh and their application performance is insufficient.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A transition metal carbonitride-SiC x N y A method for preparing a composite ceramic comprises:
[0007] The MeSi2 powder and carbon powder are mixed and ball-milled uniformly, and then further ground after drying to obtain a fully mixed and uniform powder mixture;
[0008] Pressing the powder mixture into a ceramic body by cold pressing;
[0009] The ceramic body is subjected to high temperature heat treatment in a nitrogen environment, and then cooled to obtain transition metal carbonitride-SiC x N y Composite ceramics;
[0010] In the MeSi2, Me is a transition metal.
[0011] Furthermore, in the MeSi2, Me is a mixture of one or more phases of Hf, Zr, Ta, Ni, and Ti.
[0012] Furthermore, the mixing molar ratio of the MeSi2 powder to the carbon powder is 1-5:1-5.
[0013] Furthermore, during the ball milling process, the ball-to-material ratio is 2:1, the ball milling medium is anhydrous ethanol, and the mass ratio of the anhydrous ethanol to the mixed powder of MeSi2 powder and carbon powder is 2 to 3:1.
[0014] Furthermore, during the ball milling process, the rotation speed is 200 to 500 rpm and the ball milling time is 4 to 6 hours.
[0015] Furthermore, the drying temperature is 60-100° C., and the drying time is 8-18 hours.
[0016] Furthermore, the cold pressing process includes:
[0017] The powder mixture is poured into a tabletting mold with a diameter of Φ10 to Φ30 mm, and the pressure is maintained at 4 to 15 MPa for 1 to 30 minutes to obtain a ceramic embryo with a diameter of Φ10 to Φ30 mm.
[0018] Furthermore, the heating rate of the high temperature heat treatment is 2-10°C / min, the heat treatment temperature is 1500-1800°C, and the heat treatment time is 1-3h.
[0019] Furthermore, the cooling process is: cooling to 300° C. at a rate of 2 to 10° C., and then cooling to room temperature.
[0020] Transition metal carbonitride-SiC prepared by the preparation method x N y Composite ceramics.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a transition metal carbonitride-SiC x N y The preparation method of composite ceramics adopts nitridation heat treatment method, uses transition metal disilicide and C powder as raw materials, and reacts at high temperature in nitrogen atmosphere to generate transition metal carbonitride-SiC x N y (y can be 0) composite ceramics. In the process of preparing transition metal carbonitride ceramics, SiC is generated simultaneously. x N y Compared with single-phase ceramics, the sintering performance of composite ceramics is greatly improved due to the presence of the second phase, and the strength and toughness are improved. In particular, silicon-based composite carbide ceramics have the advantages of a wide service temperature range and good process adaptability. At the same time, due to the self-healing effect of SiO2 and the formation of low oxygen permeability silicate glass, silicon-based composite carbide ceramics also show better anti-ablation performance, realizing the wide temperature range and high temperature range application of transition metal carbonitrides. Based on the present invention, transition metal carbonitride-SiCx N y Preparation and performance improvement of composite ceramics, SiC x N y It has potential applications in electromagnetic microwaves. Through the design of raw material ratios and process parameters, it is expected to achieve functional applications of such composite ceramics. Therefore, the development prospects of the present invention are very promising, and the economic and social benefits are very outstanding.
[0023] The present invention adopts the nitridation heat treatment method to prepare the transition metal carbonitride-SiC x N y The phase distribution of composite ceramics is uniform, compared with the existing HfC x N y Ceramic preparation process, HfC in the composite ceramic x N y The introduction method is simple and low cost. In high temperature oxygen environment, it has excellent ablation resistance. Transition metal carbonitrides have extremely high melting enthalpy, excellent high temperature stability and ablation resistance. In addition, SiC x N y The introduction of makes the composite ceramics applicable to different high-temperature environments. In addition, Si-Me-CN nanowires are formed on the surface of the sample, which is beneficial to the thermal conduction of the sample surface temperature, reduces the ablation surface temperature, and further improves the ablation resistance of the composite ceramics. At the same time, compared with transition metal carbide or nitride ceramics, transition metal carbonitride ceramics have higher hardness, certain toughness and ductility, and their anti-erosion performance is better. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 The transition metal carbonitride-SiC of the present invention x N y Flow chart of the preparation process of composite ceramics.
[0026] Figure 2 HfC prepared in Example 1 of the present invention x N y -SiC x N y Low magnification SEM image of composite ceramics.
[0027] Figure 3 HfC prepared in Example 1 of the present inventionx N y -SiC x N y High-magnification SEM image and corresponding EDS spectrum of the composite ceramic, where (a) is the high-magnification SEM image and (b) is the EDS spectrum.
[0028] Figure 4 HfC prepared in Example 1 of the present invention x N y -SiC x N y XRD pattern of composite ceramics.
[0029] Figure 5 HfC prepared in Example 2 of the present invention x N y -SiC x N y Macroscopic image of the surface of composite ceramic after oxyacetylene torch ablation.
[0030] Figure 6 HfC prepared in Example 3 of the present invention x N y -SiC x N y High-magnification SEM image of the cross section of the composite ceramic. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0032] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0033] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0034] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0035] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0039] See also Figure 1 The present invention provides a transition metal carbonitride-SiC x N y The preparation method of the composite ceramic comprises the following steps:
[0040] Step 1: Mix MeSi2 powder and carbon powder in a molar ratio of 1-5:1-5, where Me in MeSi2 is a mixture of one or more phases of Hf, Zr, Ta, Ni, and Ti. Put the powder mixture and zirconium oxide grinding balls into a corundum ball mill, where the ball-to-material ratio is 2:1, add anhydrous ethanol as a ball milling medium into the ball mill, and the mass ratio of the ethanol to the powder is 2-3:1, then seal the corundum ball mill, and use a planetary ball mill to perform ball milling at a speed of 200-500rpm. After ball milling for 4-6 hours, pour the powder solution into a beaker, place it in an electric hot air drying oven at a temperature of 60-100°C and dry it for 8-18 hours, and further grind the dried powder with an agate mortar for 20-40 minutes to obtain a fully mixed and uniform powder mixture.
[0041] Step 2: Pour the powder mixture into a tabletting mold with a diameter of Φ10 to Φ30 mm, and use a cold pressing process at a pressure of 4 to 15 MPa for 1 to 30 minutes to obtain a ceramic embryo with a diameter of Φ10 to Φ30 mm.
[0042] Step 3: Place a layer of graphite paper on the inner wall of the Al2O3 crucible, place the ceramic body into the alumina crucible, and then place the crucible in the center section of the tubular furnace for high-temperature heat treatment in a nitrogen environment. Before heating, first pass nitrogen for gas washing to remove oxygen in the furnace and prevent the occurrence of side reactions. After the gas washing is completed, nitrogen is introduced, and the temperature in the furnace is raised to 1500-1800°C at a rate of 2-10°C / min. After keeping warm for 1-3 hours, it is cooled to 300°C at a rate of 2-10°C / min, and then cooled to room temperature with the furnace. Take out the sample to obtain transition metal carbonitride-SiC x N y Composite ceramics.
[0043] The present invention is further described in detail in the following crucible specific embodiments:
[0044] Embodiment 1:
[0045] Step 1: Mix HfSi2 powder and carbon powder in a molar ratio of 1:1, put the powder mixture and zirconium oxide grinding balls into a corundum ball mill, where the ball-to-material ratio is 2:1, add anhydrous ethanol as a ball milling medium into the ball mill, and its mass ratio to the powder is 3:1, then seal the corundum ball mill, and use a planetary ball mill to perform ball milling at a speed of 400 rpm. After ball milling for 4 hours, pour the powder solution into a beaker, place it in an electric blast drying oven at a temperature of 70°C and dry it for 15 hours, and further grind the dried powder with an agate mortar for 20 minutes to obtain a fully mixed and uniform powder mixture.
[0046] Step 2: Pour the powder mixture into a tabletting mold with a diameter of Φ10 mm, and use a cold pressing process at a pressure of 12 MPa for 10 minutes to obtain a ceramic body with a diameter of 10 mm.
[0047] Step 3: Place a layer of graphite paper on the inner wall of the Al2O3 crucible, place the ceramic body in the alumina crucible, and then place the crucible in the center of the tubular furnace for high-temperature heat treatment in a nitrogen environment. Before heating, nitrogen is first passed through for gas washing to remove oxygen in the furnace to prevent the occurrence of side reactions. After the gas washing is completed, nitrogen is passed through, and the temperature in the furnace is raised to 1600°C at a rate of 5°C / min. After keeping warm for 2h, it is cooled to 300°C at a rate of 4°C / min, and then cooled to room temperature with the furnace. The sample is taken out to obtain HfC x N y -SiC x N y Composite ceramics.
[0048] The HfC prepared in this example x N y -SiC x N y Low-power SEM images of composite ceramics are shown in Figure 2. Figure 2 As shown, Figure 2 Analysis shows that the surface phase of the sample is evenly distributed. Combining EDS energy spectrum element analysis and X-ray diffraction pattern analysis, such as Figure 3 and Figure 4 As shown, it can be seen that white HfC is formed on the surface of the sample x N y Crystalline and black amorphous SiC x N y In addition, Si-Hf-CN nanowires were formed on the sample surface. Therefore, it can be judged that HfC x N y -SiC x N y Composite ceramics.
[0049] Embodiment 2:
[0050] Step 1: Mix HfSi2 powder and carbon powder in a molar ratio of 1:3, put the powder mixture and zirconium oxide grinding balls into a corundum ball mill, where the ball-to-material ratio is 2:1, add anhydrous ethanol as a ball milling medium into the ball mill, and its mass ratio to the powder is 3:1, then seal the corundum ball mill, and use a planetary ball mill to perform ball milling at a speed of 400 rpm. After ball milling for 5 hours, pour the powder solution into a beaker, place it in an electric blast drying oven at a temperature of 70°C and dry it for 17 hours, and further grind the dried powder with an agate mortar for 30 minutes to obtain a fully mixed and uniform powder mixture.
[0051] Step 2: Pour the powder mixture into a tabletting mold with a diameter of Φ10 mm, and use a cold pressing process at a pressure of 12 MPa for 10 minutes to obtain a ceramic body with a diameter of 10 mm.
[0052] Step 3: Place a layer of graphite paper on the inner wall of the Al2O3 crucible, place the ceramic body in the alumina crucible, and then place the crucible in the center of the tubular furnace for high-temperature heat treatment in a nitrogen environment. Before heating, nitrogen is first passed through for gas washing to remove oxygen in the furnace to prevent the occurrence of side reactions. After the gas washing is completed, nitrogen is passed through, and the temperature in the furnace is raised to 1700°C at a rate of 3°C / min. After keeping warm for 2h, it is cooled to 300°C at a rate of 4°C / min, and then cooled to room temperature with the furnace. The sample is taken out to obtain HfC x N y -SiC x N yComposite ceramics.
[0053] According to the GJB-323A96 standard, the HfC prepared in this embodiment x N y -SiC x N y Composite ceramics were subjected to oxyacetylene torch ablation test at 2.4MW / m 2 After 60s of ablation under heat flux, a white oxide film formed on the surface of the sample, such as Figure 5 As shown, it can be found that the oxide film on the surface of the sample after ablation is smooth and dense, without defects such as cracks.
[0054] Embodiment three:
[0055] Step 1: Mix HfSi2 powder and carbon powder in a molar ratio of 1:5, put the powder mixture and zirconium oxide grinding balls into a corundum ball mill, where the ball-to-material ratio is 2:1, add anhydrous ethanol as a ball milling medium into the ball mill, and its mass ratio to the powder is 3:1, then seal the corundum ball mill, and use a planetary ball mill to perform ball milling at a speed of 400 rpm. After ball milling for 5 hours, pour the powder solution into a beaker, place it in an electric blast drying oven at a temperature of 70°C and dry it for 17 hours, and further grind the dried powder with an agate mortar for 30 minutes to obtain a fully mixed and uniform powder mixture.
[0056] Step 2: Pour the powder mixture into a tabletting mold with a diameter of Φ10 mm, and use a cold pressing process at a pressure of 12 MPa for 10 minutes to obtain a ceramic body with a diameter of 10 mm.
[0057] Step 3: Place a layer of graphite paper on the inner wall of the Al2O3 crucible, place the ceramic body in the alumina crucible, and then place the crucible in the center of the tubular furnace for high-temperature heat treatment in a nitrogen environment. Before heating, nitrogen is first passed through for gas washing to remove oxygen in the furnace to prevent the occurrence of side reactions. After the gas washing is completed, nitrogen is passed through, and the temperature in the furnace is raised to 1600°C at a rate of 4°C / min. After keeping warm for 2h, it is cooled to 300°C at a rate of 3°C / min, and then cooled to room temperature with the furnace. The sample is taken out to obtain HfC x N y -SiC x N y Composite ceramics.
[0058] The HfC prepared in this example x N y -SiC x N y The cross-sectional high-magnification SEM images of the composite ceramics were analyzed, such as Figure 6 As shown, it can be seen that white HfC is formed inside the sample x Ny phase, black SiC phase and black-gray SiC x N y Therefore, it can be judged that this embodiment obtains HfC x N y -SiC x N y Composite ceramics.
[0059] Embodiment 4:
[0060] Step 1: Mix HfSi2 powder and carbon powder in a molar ratio of 1:2, put the powder mixture and zirconium oxide grinding balls into a corundum ball mill, where the ball-to-material ratio is 2:1, add anhydrous ethanol as a ball milling medium into the ball mill, and its mass ratio to the powder is 2:1, then seal the corundum ball mill, and use a planetary ball mill to perform ball milling at a speed of 400 rpm. After ball milling for 5 hours, pour the powder solution into a beaker, place it in an electric blast drying oven at a temperature of 70°C and dry it for 17 hours, and further grind the dried powder with an agate mortar for 30 minutes to obtain a fully mixed and uniform powder mixture.
[0061] Step 2: Pour the powder mixture into a tabletting mold with a diameter of Φ20 mm, and use a cold pressing process at a pressure of 14 MPa for 10 minutes to obtain a ceramic body with a diameter of 20 mm.
[0062] Step 3: Place a layer of graphite paper on the inner wall of the Al2O3 crucible, place the ceramic body in the alumina crucible, and then place the crucible in the center of the tubular furnace for high-temperature heat treatment in a nitrogen environment. Before heating, nitrogen is first passed through for gas washing to remove oxygen in the furnace to prevent the occurrence of side reactions. After the gas washing is completed, nitrogen is passed through, and the temperature in the furnace is raised to 1500°C at a rate of 3°C / min. After keeping warm for 2.5 hours, it is cooled to 300°C at a rate of 3°C / min, and then cooled to room temperature with the furnace. The sample is taken out to obtain HfC x N y -SiC x N y Composite ceramics.
[0063] Embodiment five:
[0064] Step 1: Mix ZrSi2 powder and carbon powder in a molar ratio of 1:3, put the powder mixture and zirconium oxide grinding balls into a corundum ball mill, where the ball-to-material ratio is 2:1, add anhydrous ethanol as a ball milling medium into the ball mill, and its mass ratio to the powder is 2:1, then seal the corundum ball mill, and use a planetary ball mill to perform ball milling at a speed of 400 rpm. After ball milling for 4 hours, pour the powder solution into a beaker, place it in an electric blast drying oven at a temperature of 70°C and dry it for 15 hours, and further grind the dried powder with an agate mortar for 20 minutes to obtain a fully mixed and uniform powder mixture.
[0065] Step 2: Pour the powder mixture into a tabletting mold with a diameter of Φ20 mm, and use a cold pressing process at a pressure of 12 MPa for 10 minutes to obtain a ceramic body with a diameter of 20 mm.
[0066] Step 3: Place a layer of graphite paper on the inner wall of the Al2O3 crucible, place the ceramic body in the alumina crucible, and then place the crucible in the center of the tube furnace for high-temperature heat treatment in a nitrogen environment. Before heating, nitrogen is first passed through for gas washing to remove oxygen in the furnace to prevent the occurrence of side reactions. After the gas washing is completed, nitrogen is passed through, and the temperature in the furnace is raised to 1500℃ at a rate of 5℃ / min. After keeping warm for 2.5h, it is cooled to 300℃ at a rate of 4℃ / min, and then cooled to room temperature with the furnace. The sample is taken out to obtain ZrC x N y -SiC x N y Composite ceramics.
[0067] The present invention uses transition metal disilicide and C powder as raw materials, adopts nitridation heat treatment method, and generates transition metal carbonitride-SiC by high temperature reaction under nitrogen atmosphere. x N y (y can be 0) composite ceramics. High temperature reaction in nitrogen atmosphere can effectively prevent oxidation of raw materials during heating and ensure the stability of chemical composition and structure of the product. Nitrogen is also one of the reactants to participate in the formation of transition metal carbonitrides and SiC x N y Ceramic phase. During the preparation of transition metal carbonitride ceramics, SiC x N y As the second phase, the ceramic phase can significantly improve the sintering performance. The presence of the second phase helps to promote the bonding between grains and improve the density and strength of the sintered body. x N yThe multiphase structure of composite ceramics gives them higher strength and toughness. The presence of the second phase can also disperse and absorb stress, prevent crack expansion, and thus improve the overall mechanical properties of the material. The interface formed between different phases in the composite ceramics can produce an interface effect, which helps to further improve the strength and toughness of the material. In addition, under high temperature conditions, transition metal carbonitride-SiC x N y The composite ceramics also exhibit excellent thermal stability and oxidation resistance. x N y Composite ceramics have broad application prospects in aerospace, energy, chemical industry and other fields.
[0068] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A transition metal carbonitride-SiC x N y A method for preparing a composite ceramic, characterized in that: include: The MeSi2 powder and carbon powder are mixed and ball-milled uniformly, and then further ground after drying to obtain a fully mixed and uniform powder mixture; Pressing the powder mixture into a ceramic body by cold pressing; The ceramic body is subjected to high temperature heat treatment in a nitrogen environment, and then cooled to obtain transition metal carbonitride-SiC x N y Composite ceramics; In the MeSi2, Me is a transition metal.
2. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: In the MeSi2, Me is a mixture of one or more phases of Hf, Zr, Ta, Ni, and Ti.
3. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: The mixing molar ratio of the MeSi2 powder to the carbon powder is (1-5):(1-5).
4. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: During the ball milling process, the ball-to-material ratio is 2:1, the ball milling medium is anhydrous ethanol, and the mass ratio of the anhydrous ethanol to the mixed powder of MeSi2 powder and carbon powder is (2-3):
1.
5. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: During the ball milling process, the rotation speed is 200-500 rpm and the ball milling time is 4-6 hours.
6. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: The drying temperature is 60-100° C., and the drying time is 8-18 hours.
7. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: The cold pressing process comprises: The powder mixture is poured into a tabletting mold with a diameter of Φ10 to Φ30 mm, and the pressure is maintained at 4 to 15 MPa for 1 to 30 minutes to obtain a ceramic embryo with a diameter of Φ10 to Φ30 mm.
8. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: The heating rate of the high temperature heat treatment is 2-10°C / min, the heat treatment temperature is 1500-1800°C, and the heat treatment time is 1-3h.
9. A transition metal carbonitride-SiC according to claim 1 x N y A method for preparing a composite ceramic, characterized in that: The cooling process is: cooling to 300° C. at a rate of 2-10° C., and then cooling to room temperature.
10. Transition metal carbonitride-SiC prepared by the preparation method according to any one of claims 1 to 9 x N y Composite ceramics.
Citation Information
Patent Citations
Preparation method of three-dimensional hafnium carbide-titanium silicon carbide multiphase ceramic
CN110282976A
Long-time ablation-resistant ultrahigh-melting-point nitrogen-containing carbide ultrahigh-temperature ceramic and application thereof
CN111072388A
Method for preparing carbonitride-silicide solid solution composite ceramic at low temperature by reaction hot pressing sintering technology
CN113999013A
Self-healing ultrahigh-temperature high-entropy carbon nitrogen compound ceramic as well as preparation method and application thereof
CN115043657A
Method for preparing a carbide ceramics multilayer coating on, and optionally in, a part made of a carbon-containing material using a reactive melt infiltration RMI technique
US20160040299A1
Cited By
Hafnium carbonitride-silicon carbide-transition metal carbide composite ceramic and preparation method thereof
CN122233794A
